The doctrinal metaphor porta clausa in medieval liturgical hymns and its reflection in the iconography of the Annunciation - Salvador-González, José María (De Medio Aevo, 2025)
Focused on investigating some interpretations of the vision of the prophet Ezekiel about the eastern shut gate of the temple that was to be rebuilt in Jerusalem, this article] seeks two objectives. First, to present many fragments of medieval liturgical hymns in Latin that interpret the Ezekiel’s sentence in a Mariological and Christological sense. Second, to analyze seven artistic representations of the Annunciation that include a shut door in their scene. The comparative analysis between these hymnic texts and these artistic images allows us to conclude that both reflect the same doctrinal meanings.